PENCEMARAN AIR SUNGAI REMU KAITANNYA DENGAN PENGGUNAAN LAHAN DAN AKTIVITAS MASYARAKAT DI DAS REMU KOTA SORONG PROVINSI PAPUA BARAT - , DESI NATALIA LAZARUS, Prof. Dr. Suratman, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
River basin that should serve as conservation functions, rainfall catchment area and which is dominated by forest stands, currently has shifted to agri-business and settlement purposes. This fact has affected the environment quality, one of them is the water quality of River Remu. This research aimed to (1) analyze the physical, chemical, and biological properties of River Remu water, (2) evaluate the effects of land use and community activities on the water quality of River Remu. Explorative method with survey approach was adopted in this research. Data collected through the use of literature study, field observation, interviews in terms of questionnaires and laboratory analysis. Population involved residents of Remu river basin, while water samples were taken based on âpurposive samplingâ method at four stations according to land use /pollution sources/river branching. At individual station, sampling was conducted at one point with two times of replication, i.e. in the morning from 06:00 to 08:00 am WIT (East Indonesian Time Zone) and in the afternoon from 16:00 to 18:00 pm WIT